COVID-19 Vaccine Acceptance from the Perspective of People Living in Northern Thailand: A Mixed Methods Research - Payaprom, Yupares; Tantipong, Hutsaya; Manasatchakun, Pornpun; Chandeekeawchakool, Sarinyaporn; Khamchai, Songyos (Nursing Journal CMU, 2022)
This research aimed to determine the acceptance rate of the COVID-19 vaccine and its associated factors. A mixed method research study was conducted with the quantitative study comprised of 2,200 adults aged 18 or older. Participants were recruited from households in 25 districts in Chiang Mai province, with a multi-stage cluster sampling method. Data were collected using a questionnaire based on the Health Belief Model (HBM). Binary logistic regression analysis was performed to identify factors associated with COVID-19 vaccine acceptance rates. For the qualitative portion of the study, a purposive sampling approach was utilized to recruit 40 adults aged 18 or older. Focus group discussions were conducted, and qualitative content analysis was applied to analyze data. The research results indicated that the COVID-19 vaccine acceptance rate was 41.1%. The factors associated with the acceptance of COVID-19 vaccines were sociodemographic characteristics including education level, employment status, influenza vaccination history, having good knowledge about COVID-19, perceived risk of contracting COVID-19, perceived benefits of the vaccine, and receiving cues to action, such as being encouraged by community members or recommendations from healthcare professionals. The focus groups also revealed that participants’ decisions in relation to the acceptance of COVID-19 vaccines were based on several factors including salience of risk, efficacy and safety of the COVID-19 vaccine, Information needs and sources of information, and influence of others. These findings emphasize the importance of considering and understanding the factors that affect people’s vaccination decisions in order to develop effective public health initiatives to increase COVID-19 vaccination uptake.